Ethnogastronomic elements as an agroecological tourism offer in the Calderas parish, Barinas State, Venezuela - Fernández, Alfonso (2024)
Ethnogastronomy, exploring the relationship between food and culture, revealing the identity of communities. This study focused on identifying the ethnogastronomic elements of the Calderas parish, Barinas, to propose them as an agroecological tourism offer. Through in-depth interviews with residents with experience in the culinary area, a rich gastronomic heritage was identified by a diversity of local products, ancestral techniques and typical dishes that make up a unique culinary identity. Ingredients such as Caldera nuts, conopia and cocoa offer the possibility of creating authentic and attractive gastronomic experiences for tourists. Agroecological tourism is presented as an opportunity to diversify the local economy, generate income and strengthen the social fabric. The marketing of local products, the offer of tourist services and the promotion of sustainable agricultural practices are key to attracting a segment of tourists increasingly interested in authentic and sustainable experiences. It is essential to take advantage of this moment and strengthen the organization, promotion and training to consolidate agroecological tourism as a driver of local development.